1996
DOI: 10.1016/s0092-8674(00)81365-3
|View full text |Cite
|
Sign up to set email alerts
|

A Complex of NuMA and Cytoplasmic Dynein Is Essential for Mitotic Spindle Assembly

Abstract: NuMA is a nuclear protein during interphase but redistributes to the spindle poles early in mitosis. To investigate its role during spindle formation, we tested spindle assembly in frog egg extracts from which NuMA was immunodepleted. Immunodepletion revealed that NuMA forms a complex with cytoplasmic dynein and dynactin. The depleted extracts failed to assemble normal mitotic spindles, producing, instead, chromatin-associated irregular arrays of microtubules lacking characteristic spindle poles. A subdomain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
536
2
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 554 publications
(559 citation statements)
references
References 43 publications
18
536
2
3
Order By: Relevance
“…NuMA is required to tether centrosomes to spindle poles and to organize microtubule minus ends at spindle poles in vertebrate cells (Gaglio et al, 1995;Merdes et al, 1996;Gordon et al, 2001). Surprisingly, we show that perturbation of Kid function permits centrosomes to remain tethered to the spindle and microtubule minus ends to remain focused at spindle poles despite the perturbation of NuMA function.…”
Section: Spindle Organizationmentioning
confidence: 72%
See 2 more Smart Citations
“…NuMA is required to tether centrosomes to spindle poles and to organize microtubule minus ends at spindle poles in vertebrate cells (Gaglio et al, 1995;Merdes et al, 1996;Gordon et al, 2001). Surprisingly, we show that perturbation of Kid function permits centrosomes to remain tethered to the spindle and microtubule minus ends to remain focused at spindle poles despite the perturbation of NuMA function.…”
Section: Spindle Organizationmentioning
confidence: 72%
“…However, several observations support the view that antibody injection completely and specifically inhibited the activities of both Kid and NuMA. First, defects in chromosome alignment and spindle morphology generated by injection of antibodies to either Kid or NuMA are equivalent to the effects observed upon the complete depletion of either of these proteins from extracts prepared from frog eggs (Merdes et al, 1996;Antonio et al, 2000;Funabiki and Murray, 2000). Second, the relationship between Kid and NuMA is specific because simultaneous injection of antibodies to Kid and either HSET or CENP-E showed no significant differences from injection of each antibody alone.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, their ability to directly anchor components of the ␥ TuRC and thus serve as molecular scaffolds for tethering these complexes to centrosomes has not been demonstrated. These include the centrosome proteins Asp (do Carmo Avides and Glover, 1999), NuMA (Merdes et al, 1996), TPX-2 (Wittmann et al, 2000;Garrett et al, 2002), SPD-5 (Hamill et al, 2002), PCM-1 (Dammermann and Merdes, 2002), Sas-4 (Kirkham et al, 2003) centrosomin (Megraw et al, 1999;Terada et al, 2003), and several regulatory molecules, including Aurora A (Hannak et al, 2001;Giet et al, 2002), Polo (Lane and Nigg, 1996;Barbosa et al, 2000), PP1 (Katayama et al, 2001), and PP4 (Sumiyoshi et al, 2002).…”
Section: Other Proteins Involved In Centrosomal ␥ Turc Anchoring and mentioning
confidence: 99%
“…A number of scaffold proteins have been identified that associate with the mitotic spindle and play important roles in spindle assembly and cell cycle control. Examples of these proteins include γ-tubulin, NuMA, TPX2, dynactin and nucleolar spindle-associated protein (NuSAP) (Merdes et al, 1996;Hetzer et al, 2000). NuSAP is a wellknown microtubule-associated protein.…”
Section: Introductionmentioning
confidence: 99%